INTERDEPENDENSI KOMUNITAS INTELIJEN DALAM FORUM KERJA SAMA KEIMIGRASIAN DI KAWASAN ASIA TENGGARA: ANALISIS TERHADAP UPAYA KONTRATERORISME GUNA MEREDUKSI JARINGAN FOREIGN TERRORIST FIGHTER - Yusuf, Muhammad Choirul; Afsholikhati, Imania; Pangesti, Rizkyana Mutia; Amrullah, Damarjati Mahatma (Jurnal Ilmiah Kajian Keimigrasian, 2025)
Immigration has a crucial role in maintaining the country's security and sovereignty. The Southeast Asia region, which includes Indonesia, is a transit point that is vulnerable to organized transnational crime, especially terrorism. The Institute for Economics and Peace (IEP) has collected data on the global terrorism index (GTI) in ASEAN countries, and the results show that 6 out of 10 countries in Southeast Asia have a threat of terrorism. Indonesia is a potential target because it has the largest Muslim population in the world. The Ministry of Law and Human Rights, through the immigration institution, is in the spotlight because it has authority in matters of people's crossing, border management and immigration law enforcement. Southeast Asia, which is rich in cultural, ethnic, religious, political and social diversity, as well as cross-border mobility, provides opportunities for terrorist syndicates to migrate through non-procedural vulnerable points. Therefore, cooperation and intelligence monitoring are very important in mitigating and handling terrorism in Southeast Asia, through regional cooperation forums as a means to facilitate interaction between countries. Immigration institutions need to collaborate at a diplomatic and tactical level, as well as increase interconnection with the intelligence community in Southeast Asia to reduce terrorist networks. Intelligence supervision is also needed to identify terrorist networks early on, while intelligence cooperation enables the exchange of information about the movements of terrorist groups and preventive steps that can be taken.